–6х – 13 = –7х – 14 5х = 8 + 3(2х + 3) 3(4х + 1) + 3х = 2х – 2 7(2х – 5) – 4(5х + 3) = –33 6х – 7(3х – 5) – 2(4х – 7) = 3 12(x – 2) – (4x – 3) = 8(x + 3)  Решите пожалуйста!

–6х – 13 = –7х – 14 5х = 8 + 3(2х + 3) 3(4х + 1) + 3х = 2х – 2 7(2х – 5) – 4(5х + 3) = –33 6х – 7(3х – 5) – 2(4х – 7) = 3 12(x – 2) – (4x – 3) = 8(x + 3)  Решите пожалуйста!
Гость
Ответ(ы) на вопрос:
Гость
-6х-13=-7х-14 7х-6х=13-14 х=-1 5х=8+3(2х+3) 5х=8+6х+9 5х-6х=17 -х=17 х=-17 3(4х+1)+3х=2х-2 12х+3+3х=2х-2 15х-2х=-3-2 13х=-5 х=5/13 7(2х-5)-4(5х+3)=-33 14х-35-20х-12=-33 -6х=35+12-33 -6х=14 -х=14/6 -х=2 2/6 -х=2 1/3 6х-7(3х-5)-2(4х-7)=3 6х-21х+35-8х+14=3 -23х=3-35-14 -23х=-46 х=46:23 х=2 12(х-2)-(4х-3)=8(х+3) С этим уравнением... не уверена в ответе, поэтому не пишу. Удачи.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы